ANALISIS ELASTISITAS TRANSMISI HARGA TANDAN BUAH SEGAR PT JAMIKA RAYA DAN KOPERASI UNIT DESA DI KECAMATAN LIMBURLUBUK MENGKUANG DAN KECAMATAN BATHIN II PELAYANG KABUPATEN BUNGO - Misra Yeni.R; Ronald N Girsang (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research was conducted to analyze the transmission transmission rates of village cooperative units in Limbur Lubuk Mengkuang sub-district and Bathin II Pelayang Regency sub-district and to analyze the transmission elasticity of PT Jamika Raya's fresh fruit bunches and cooperatives village unit in Limbur Lubuk Mengkuang sub-district and Bathin II Pelayang Regency sub-district. This research was carried out from January 1, 2018 to December 31, 2018. This study uses secondary data with a time series from 2010 to 2015 (monthly data) Data analysis used descriptive analysis and linear regression. The results showed that Fresh Fruit Bunches in Village Cooperative Units fluctuated, the farther the distance from PT Jamika Raya, the prices that farmers would get were cheaper and closer to the price of PT Jamika Raya expensive.